Experimental Study on Mechanical Properties of Mask-Improved Calcareous Sand - Longwen Zhang; Zhuoyi Sun; Baohua Liu; Zongtang Zhang; Junqi Zhang (Applied Sciences)
Due to the widespread prevalence of respiratory diseases such as COVID-19 and H1N1, the use of disposable masks has increased significantly. Consequently, the environmental issues arising from their accumulation have become increasingly severe. This study, therefore, aims to investigate the potential of using masks as soil reinforcement materials. This study conducted triaxial and seepage tests on mask–calcareous sand mixtures with varying ratios to examine the effects of mask content on the strength, modulus, particle fragmentation, and permeability coefficient of calcareous sand, as well as the influence of different mask sizes on shear strength and shear dilation. The results demonstrate that with an increase in mask content, the peak stress ratio of the mask–calcareous sand mixture increases by 4% per level, and the internal friction angle rises by approximately 1.6% per level. Conversely, water permeability and shear swelling are reduced, and particle loss decreases by over 70%. The reinforcing effect of the mask is attributed to the high friction between the mask and the calcareous sand at the contact interface, which restricts the movement of soil particles during deformation, thereby enhancing the overall strength of the mixture. Among the three mask sizes, the smallest mask–calcareous sand mixture exhibited the greatest improvement in shear strength, and the shear shrinkage effect was more pronounced. This indicates that particle size also significantly influences the mechanical properties of the mixtures. The reinforcing effect of the mask on the soil results from the high friction at the interface between the mask and the calcareous sand. When the soil deforms, the mask enhances the overall strength of the mixture by restricting the movement of soil particles. Considering the impact of masks on the performance of calcareous sand, it can be concluded that the optimal mass content of masks is 0.3%. This study offers a new perspective on the reuse of discarded masks in civil engineering applications.